Influenza hospitalizations in children under 1 year old in Spain: the importance of maternal immunization - Jesús San Román Montero; Ruth Gil-Prieto; Rubén Jiménez Martín; Raúl Ortiz de Lejarazu; Carmen Gallardo-Pino; Angel Gil de Miguel (Taylor & Francis Group, 2021)
This study estimates the burden of influenza in infants up to 12 months of age in Spain over 8 seasons (2009/10-2016/17). The survey was conducted by reviewing the Spanish Surveillance System for Hospital Data. Over the eight seasons, 5,618 hospital admissions were recorded for patients younger than 12 months that included codes related to influenza in any diagnostic position (487-488 ICD-9-CM and J9, J10 and J11 CIE 10). In total, 2,363 admissions (42.1%) were female patients whose median age was 3.05 months. Patients younger than 6 months accounted for 3,856 admissions (68.6%). Among them, 59.2% were male, and 40.8% were female (p < .05). Overall, 37.1% (2,084 patients) were younger than 2 months. The hospitalization rate for the entire period studied was 156.09 admissions per 100,000 children under 12 months of age (95% CI: 152.4-160.6). The average duration of hospitalization was 6.6 days (95% CI: 6.4-6.8). Eighteen deaths were recorded for hospitalized patients over the entire period. Of these, 12 patients (66.7%) were younger than 6 months. There is a significant burden of influenza disease in children under 1 year of age in Spain, mainly in children under 6 months of age. Improvements to prevention strategies through increased vaccination coverage in family environments and vaccination strategies involving pregnant woman can contribute decisively and effectively to reducing these hospitalizations.